Neutrophil-binding immunoglobulin G in systemic lupus erythematosus. - Starkebaum, G (1979)
The objectives of these studies were to quantify the amounts of immunoglobulin (Ig)G bound to peripheral blood neutrophils from patients with systemic lupus erythematosus (SLE) and to determine the contributions of soluble immune complexes or anticell antibodies to the levels of IgG neutrophil-binding activity in SLE sera. Neutrophil-bound IgG, determined by a sensitive antiglobulin inhibition assay, was elevated in 7 out of 14 SLE patients compared with values obtained in 23 normal controls. The levels of IgG neutrophil-binding activity in sera were elevated in 22 of 38 patients with SLE over the values seen with 36 normal sera. No correlation was found between the peripheral blood neutrophil counts in the SLE patients and the values for IgG adherent to the cells or serum cell-binding activity. The sera from 18 patients with SLE were fractionated by gel filtration. Elevated levels of IgG neutrophil-binding activity were found in 11 of the 18 G-200 excluded pools and in 13 of the G-200 IgG pools. In nine sera elevated levels were observed in both pools. F(ab')2 fragments of IgG from SLE sera bound to normal polymorphonuclear leukocytes in greater amounts than F(ab')2 fragments of IgG from normal sera. A significant correlation existed between the values of IgG neutrophil-binding activity found in SLE sera and those obtained with both the G-200 excluded and IgG pools. Sucrose density gradient fractionation of four sera from SLE patients confirmed the presence of both large (greater than 19S) and intermediate-sized (7S-19S) cell-binding immune complexes as well as of monomeric IgG antibodies to neutrophils. The levels of IgG neutrophil-binding activity in the SLE sera correlated well with the results obtained with the Raji cell assay for immune complexes as well as with the titer of antibodies to nuclear antigens. These data indicate that circulating neutrophils from patients with SLE commonly have increased amounts of cell-bound IGG. The elevated levels of IgG neutrophil-binding activity in the sera of these patients are caused by both soluble immune complexes and antibodies reactive with neutrophils.